English political prints and pictorial political argument c.1640-c 1832: a study in historiography and methodology - Nicholson, Eirwen E. C. (University of Edinburgh, 1994)
This thesis is a critical evaluation of scholarship in respect to political prints, including graphic political satire and political caricature, produced or circulated in England c. 1640-c. 1830, together with related political images in other media. This study is historiographical, in that the greater part of Part I is written with reference to the secondary literature of this field and includes a bibliographical chapter. It is also methodological, in that specific problems in the study of this material are considered: the greater part of Part II addresses problems identified in the course of Part I and suggests alternative approaches to this material, by means of which future studies might avoid perpetuating these problems. Part I comprises twelve chapters; Part II, seven. An Appendix offers an outline of a projected Index to the B. M. Catalogue (the main reference work for the material). A volume of plates accompanies the text: these are not 'illustrations' as conventionally deployed, but primary evidence central to the argument of the chapters to which they belong. This thesis is the first study to attempt a synthetic review and critical analysis of scholarship in the field.
Keywords: History; Politics